Social Emotional Development Of Students With Children Outside Of Marriage At Pondok Pesantren Metal Rejoso Pasuruan - Dewi Masitah; Defi Dachlian Nurdiana; Ari Kartiko; Nafiul Huda (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2023)
This study aims to find out in depth about the social emotional development of children out of wedlock at the Pondok Pesantren Metal Rejoso Pasuruan. The informants of this research were the kiai and ustad of the Islamic Boarding School of Metal Rejoso Pasuruan and children illegitimate, in this case they were students from the pesantren. The research methodology uses descriptive phenomenology with a psychological approach. The process of collecting data through interviews, observation, and documentation. The technical analysis of the data is through the stages of Horizontalizatio, Developing clusters of meaning, Textural description, Structural description, and Essentialization. The theory as an analysis tool uses Hurlock's theory of social development. The results of this study indicate that the formation of personality and social-emotional children out of wedlock is education and training (Riyadhoh) which is implemented by kiai and accompanied by ustadz. As well as making the position of the kiai as their parents and fellow students as their siblings, so that they feel they have a family that is ready to pay attention to their social emotional development until they are adults. The implication of his theory is that real families are not bound by biological families as Hurlock argues, but by people who are able to provide a stable group of people with a feeling of security, able to be relied upon to meet their needs, a source of love and acceptance, who are not affected by what they do, guide them. teach approved social behavior, able to help solve problems faced by each child in adjustment to life, so as to achieve success in social life, accept aspirations, develop talents and abilities to be friends.